Seismic strengthening of masonry walls using bamboo components. Issue 14 (October 2019) - Xu, Qingfeng; Chen, Xi; Chen, Jian-Fei; Harries, Kent A; Chen, Lingzhu; Wang, Zhuolin
Bamboo is a sustainable green material and has been gradually applied in the construction industry; however, little research on strengthening masonry structures with bamboo has been carried out. In this article, strengthening methods using bamboo were developed including bamboo grid reinforced cement mortar layer, externally bonded bamboo mats, additional confining horizontal bamboo reinforced concrete band beams, and bamboo strips placed in mortar joints. Ten masonry walls were designed including two reference walls. Experimental results showed that all the strengthening methods can improve certain aspects of the seismic performance of masonry walls. The shear strength, deformability, and energy dissipation capacity of masonry walls strengthened with bamboo grid reinforced cement mortar and externally bonded bamboo mats were the most improved. The limit states of tested walls were discussed. Strengthened masonry structures with bamboo components are promising methods and can be used especially in remote areas.